If it's not what You are looking for type in the equation solver your own equation and let us solve it.
10+c=7
We move all terms to the left:
10+c-(7)=0
We add all the numbers together, and all the variables
c+3=0
We move all terms containing c to the left, all other terms to the right
c=-3
| 5x–8=3x+12* | | -3r+8.1=6 | | 7d+12=4d–3 | | 8+5x^2=23x | | 4(a–2)=–16 | | 12.4=a/3 | | 7=-3y | | x2+2=3 | | -3x+10(2)=11 | | (9x+9)=(5x+3) | | 3x-2+7x-4=24 | | 6x2=5x | | 1/2(6x+12)=2(5x-4) | | –a–95=4 | | 14x+23=7x+93 | | x^2-2x-27=-5x+1x2−2x−27=−5x+1 | | 168=4(6n-6) | | 70=2/5f-10 | | 0.7e=42 | | 2.5x-9.6=7.9 | | 2(3k-2)=8-(2k+6) | | 15.1-10.4=x | | -11g+3=-30 | | 6+10=a | | -8m-12=-92 | | F(x)=1/3•62 | | -119=1+6(1+7n) | | b+12.5=14 | | 5x^2-16x-240=0 | | -119=1+6(1+7n | | -5/u-6=-3 | | 6+1/3x=-9 |